KEPUTUSAN INVESTASI CRYPTOCURRENCY PADA KAUM MILLENIAL DI KOTA BATAM - Berry; Azmiana, Risca (LPPM Universitas Putera Batam, 2025)
This study was conducted to examine the factors influencing Cryptocurrency Investment Decisions among Millennials in Batam City. These factors include Overconfidence, Risk Tolerance, and Financial Experience. The research approach used is quantitative, with primary data collected through distributing questionnaires. The population in this study is 443,180, and the sample size is 100 people, determined using the Slovin formula with a margin of error of 10%. This study uses probability sampling with a random sampling method. The analysis techniques include descriptive analysis, instrument testing, classical assumption testing, multiple linear regression, and hypothesis testing, with data processing using SPSS version 25. The results show that Overconfidence, Risk Tolerance, and Financial Experience have a significant impact on Cryptocurrency Investment Decisions. In conclusion, H1 is accepted, H2 is accepted, H3 is accepted, and H4 is accepted.Keywords: overconfidence, risk tolerance, financial experience, cryptocurrency investment decision.